Step
*
of Lemma
geo-same-line-symmetry
∀[e:BasicGeometry]. ∀[a:Point]. ∀[b:{b:Point| a ≠ b} ]. ∀[c:Point]. ∀[d:{d:Point| c ≠ d} ].
  (line(a;b)=line(c;d) 
⇒ line(c;d)=line(a;b))
BY
{ (Auto THEN DSetVars THEN Unhide THEN Auto) }
1
1. e : BasicGeometry
2. a : Point
3. b : Point
4. [%4] : a ≠ b
5. c : Point
6. d : Point
7. [%2] : c ≠ d
8. line(a;b)=line(c;d)
⊢ SqStable(line(c;d)=line(a;b))
2
1. e : BasicGeometry
2. a : Point
3. b : Point
4. a ≠ b
5. c : Point
6. d : Point
7. c ≠ d
8. line(a;b)=line(c;d)
⊢ line(c;d)=line(a;b)
Latex:
Latex:
\mforall{}[e:BasicGeometry].  \mforall{}[a:Point].  \mforall{}[b:\{b:Point|  a  \mneq{}  b\}  ].  \mforall{}[c:Point].  \mforall{}[d:\{d:Point|  c  \mneq{}  d\}  ].
    (line(a;b)=line(c;d)  {}\mRightarrow{}  line(c;d)=line(a;b))
By
Latex:
(Auto  THEN  DSetVars  THEN  Unhide  THEN  Auto)
Home
Index